2011
DOI: 10.1016/j.tet.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Diversity oriented synthesis: substitution at C5 in unreactive pyrimidines by Claisen rearrangement and reactivity in nucleophilic substitution at C2 and C4 in pteridines and pyrido[2,3-d]pyrimidines

Abstract: This version is available at https://strathprints.strath.ac.uk/30205/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Several 2,4‐thibenzyl and 2,4‐dialkylamino pteridine derivatives showed antiparasite activities against T. brucei brucei when tested in cell‐based assays. The dialkylamino pteridines 66a and 66b reached MIC values of 3.1 μM, while 66c had a MIC of 6.3 μM …”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Several 2,4‐thibenzyl and 2,4‐dialkylamino pteridine derivatives showed antiparasite activities against T. brucei brucei when tested in cell‐based assays. The dialkylamino pteridines 66a and 66b reached MIC values of 3.1 μM, while 66c had a MIC of 6.3 μM …”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Phosphorylation can also lead to activation for nucleophilic substitution. In pteridines, phosphate forming activating agents such as BOP has been used to activate a series of 4‐oxo‐2‐thioalkyl‐ and 2‐amino‐4‐oxopteridines in a study of the introduction of multiple points of diversity using several different latent reactivities (27) (Scheme ). In contrast to the high temperatures typically required for halide displacement, substitution of the intermediate phosphate occurs at room temperature giving good yields over two steps for a series of primary and secondary amine nucleophiles.…”
Section: Diversity Through Nucleophilic Substitution At the Pteridinementioning
confidence: 99%
“…In passing, it is worth noting that the same study found that the BOP reaction in related pyrido[2,3‐ d ]pyrimidines was selective for a 4‐oxo over a 7‐oxo substituent, a feature that may be reproducible in pteridines. The substrate for this reaction contains an additional site for diversification, the thioether, and experiments were also carried out using this leaving group; in practice, it was possible to choose the order of substitution between C2 and C4 by choice of appropriate reagents, an attractive feature in a diversity‐oriented synthesis (27).…”
Section: Diversity Through Nucleophilic Substitution At the Pteridinementioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that this reaction is controlled by the nature of the solvent (DMF). Pyrido [2,3-d]pyrimidines have been also prepared from 2-alkylthiopyrimidines [72]. Transformation of 5-acyl-2H-pyran-2-ones with various amidines such as 1,3-binucleophiles in the presence of DBU (1,8-diazabicyclo [5.4.0]undec-7-ene) produced pyrano [2,3-d]pyrimidines [73].…”
Section: Synthesis Of Pyrimidines and Related Compoundsmentioning
confidence: 99%